Numerical Analysis of Sand Bed Degrading and Sediment Transport Rate Under Tailings Dam Break - Tian, Zhong; Yang, Hao; Wang, Wei; Cao, DeSheng (Frontiers in Earth Science, 2021)
Dam-breaking accidents in tailings ponds may result in loss of tailings, damage to the downstream bridges and houses, flooding of farmland and roads, hazards to the local environment, and even loss of property and lives. Therefore, research on dam breaks in tailings reservoirs and prediction of subsequent impacts are of great significance. This paper describes theoretical and numerical analyses of the retrogressive erosion model and calculations of the sand bed surface profile and sediment transport rate following tailings dam break events. The calculation results show that the degrading rate of the bed surface in the reservoir area reaches a maximum when the breach is formed and then rapidly decreases to a stable value. Farther away from the breach, the peak degrading rate of the bed surface is lower. The time of the peak tailings outflow rate is related to the formation of the breach. A larger breach has a shorter formation time and a greater peak flow.